The Effect of Capital Structure, Financial Literacy on Financial Reporting Efficiency Mediated by Technology Adoption in the Telecommunications Industry in Indonesia - Iskandar, Deni (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the interrelationships between capital structure, financial literacy, technology adoption, and financial reporting efficiency in the telecommunications industry in Indonesia. A quantitative research approach is adopted, utilizing structural equation modeling with data collected from telecommunications companies. Descriptive statistics, measurement model assessment, and structural model assessment are conducted to analyze the data. The results indicate significant direct effects of capital structure, financial literacy, and technology adoption on financial reporting efficiency. Furthermore, technology adoption mediates the relationships between capital structure, financial literacy, and financial reporting efficiency. These findings provide valuable insights for telecommunications companies, policymakers, regulators, investors, and industry practitioners, emphasizing the importance of optimizing capital structure, enhancing financial literacy, and leveraging advanced technologies to improve reporting practices and foster transparency and accountability within the sector.